Probiotics and oral health effects in children - SVANTE TWETMAN & CHRISTINA STECKSÉN-BLICKS (IAPD and Blackwell, 2008)
The belief that probiotic bacteria can influence health dates back to the beginning of the 20th century when the Ukrainian-born Nobel Prize laureate Elie Metchnikoff reported that Bulgarians lived longer than other populations and supposed that this was due to their consumption of fermented milk products containing viable bacteria.